p120 Catenin Is Required for the Stress Response in Drosophila. - Stefanatos, R.K.; Bauer, C.; Vidal, M. (PLoS ONE, 2013)
p120ctn is a ubiquitously expressed core component of cadherin junctions and essential for vertebrate development. Surprisingly, Drosophila p120ctn (dp120ctn) is dispensable for adherens junctions and development, which has discouraged Drosophila researchers from further pursuing the biological role of dp120ctn. Here we demonstrate that dp120ctn loss results in increased heat shock sensitivity and reduced animal lifespan, which are completely rescued by ectopic expression of a dp120ctn-GFP transgene. Transcriptomic analysis revealed multiple relish/NF-?B target genes differentially expressed upon loss of dp120ctn. Importantly, this aberrant gene expression was rescued by overexpression of dp120ctn-GFP or heterozygosity for relish. Our results uncover a novel role for dp120ctn in the regulation of animal stress response and immune signalling. This may represent an ancient role of p120ctn and can influence further studies in Drosophila and mammals.